Generalized fractional order differential equations arising in physical models - Saha Ray, Santanu; Sahoo, Subhadarshan (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This book analyzes the various semi-analytical and analytical methods for finding approximate and exact solutions of fractional order partial differential equations. It explores approximate and exact solutions obtained by various analytical methods for fractional order partial differential equations arising in physical models.
OCLC-licensed vendor bibliographic record.
Keywords: Fractional calculus; Differential equations, Partial; MATHEMATICS -- Calculus; MATHEMATICS -- Mathematical Analysis